Soviet delegates at TUC Congress, Hull, 1924 (1924)
1924 "Soviet delegates at TUC Congress, Hull, 1924" [g0882001.jpg], 1924 At the centre front is Michael Tomsky, Chair of the All Russian Central Council of Trade Unions, who was a fraternal delegate to Congress in 1924 and 1925.